Effect of placenta previa on umbilical cord hematocrit value. (30th December 2022) - Halici-Ozturk, Filiz; Beyazit, Fatma; Yakut, Kadriye; Yücel Yetiskin, Fatma Didem; Öztürk, Merve; Sinaci, Selcan; Caglar, A. Turhan
Abstract: Objective: Placenta previa is one of the causes of neonatal anemia. This condition is mainly explained by antenatal hemorrhage and incision of the anteriorly located placenta during cesarean section. However, the mechanism of neonatal anemia in placenta previa has not been extensively studied or well elucidated. This study investigates whether placenta previa is associated with lower hematocrit levels in newborns with no antenatal hemorrhage and placental incision. Key findings: This prospective study investigated 47 patients with previa and 43 control patients who gave birth with a cesarean section at 34–38 weeks of gestation. Blood samples were obtained from the fetal end of the umbilical vein. The mean umbilical cord hematocrit value was 49.3% in the control patients and 46.7% in the patients with previa, and the difference was statistically significant ( p  = .029). No significant association was observed between hematocrit value and birth weight, gestational age, newborn gender, placenta position, or preoperative maternal hemoglobin level. Conclusion: The study findings reveal that even if not complicated by antepartum or intrapartum hemorrhage, placenta previa may be associated with lower hematocrit values in newborns. Although in none of the cases, the umbilical cord hematocrit value was not as low as to be defined as anemia, this effect of previa on newborns should be considered because of the importance of iron status.